Pengaruh Pengetahuan, Persepsi, dan Kepuasan terhadap Loyalitas Anggota BMT Asy-Syafi’iyah Berkah Nasional - Wiwit Tabah Santoso; Desmon Desmon; Andi Surya; M. Renandi Ekatama; Hasbullah Hasbullah; Susi Indriyani (Penerbit Goodwood, 2025)
Purpose: This research aims to find the influence of khowledge, perception, and satisfaction on the loyalty of the BMT Asy-Syafi’iyah Berkah Nasional members. Methodology/approach: This research applies a quantitative method and field-research approach. The data is obtained from literature by reading journals, books, websites and any written sources as preliminary data for the research. In addition, it also uses observation and interviews. The primary data is obtained from questionnaires sent to members of BMT Asy-Syafi’iyah Berkah Nasional. Results/findings: The first independent variable, knowledge, has a positive and significant effect on loyalty partially. The second independent variable, perception, has a positive and significant effect on loyalty partially. The third independent variable, satisfaction, has a positive and significant effect on loyalty partially. Simultaneously, knowledge, perception, and satisfaction have a positive and significant effect on the loyalty of BMT Asy-Syafi’iyah Berkah Nasional. Conclusion: The result of the t-test (partial) using t count on the knowledge variable (X1) is 3.717 and t table is 3.182. So, t count > t count (3.182 > 3.717). Limitations: Only three independent variables were analyzed for this research, while there are more than three variables. In addition, the research only analyses statistical data and it needs deeper analyses to get better results. Contribution: Results of this research are expected to give better perspectives on which factors actually influence loyalty of members of BMT Asy-Syafi’iyah. Finally, by knowing this result, the management will get better perspective on which ones should be improved to get better performance of the company.